BIOLOGIC THERAPIES IN THYROID EYE DISEASE: FROM IMMUNOPATHOGENESIS TO CLINICAL PRACTICE - Filip Chodań; Krystian Domeracki; Dagmara Laufer; Olga Klimczak; Estera Sośniecka; Adam Miler (Archiv Euromedica, 2026)
Background Thyroid Eye Disease is a complex autoimmune inflammatory disorder associated with Graves’ disease that may lead to orbital tissue remodeling, proptosis, diplopia and vision impairment. Although intravenous glucocorticoids remain the standard first-line therapy for active moderate-to-severe disease, their limited efficacy and adverse effects have stimulated the development of targeted biologic therapies. Aim This narrative review aims to summarize and critically evaluate current and emerging biologic therapies in thyroid eye disease, with particular emphasis on their immunopathogenic targets, clinical efficacy, safety, strength of evidence, and potential role in clinical practice. Materials and methods A structured literature search was conducted in PubMed, Google Scholar, and ClinicalTrials.gov for publications from 2021 to 2026, with earlier studies included selectively when they provided essential information on pathogenesis or biologic therapy. Clinical studies, experimental studies, systematic reviews, clinical guidelines, and relevant clinical trial registrations were considered. A total of 81 sources were included. Results Biologic therapies targeting key inflammatory pathways in thyroid eye disease have shown variable clinical efficacy. Teprotumumab demonstrated the strongest evidence, significantly reducing disease activity, proptosis and diplopia, with sustained therapeutic effects. Rituximab and tocilizumab primarily improved inflammatory activity, particularly in glucocorticoid-resistant disease, although rituximab showed inconsistent results across randomized trials. Emerging agents targeting IGF-1R, IL-6, TSHR, and FcRn pathways have shown promising preliminary outcomes, while IL-17 inhibitors failed to demonstrate clinical benefit. Conclusions Biologic therapies have expanded the treatment options available for patients with moderate-to-severe thyroid eye disease and represent an important step toward more personalized management. Teprotumumab currently has the strongest evidence for improving disease activity, proptosis, and diplopia, whereas the clinical roles of rituximab, tocilizumab, and emerging biologic agents remain less clearly defined. Treatment selection should consider the strength of the available evidence, expected clinical benefit, safety profile, and individual patient characteristics. High treatment costs and limited availability remain important barriers to broader implementation in routine clinical practice.